Chronic Respiratory Symptoms among TB Survivors in a High-TB Burden Setting in Indonesia: A Preliminary Study - Dewi, Intan Mauli Warma; Fauziyyah, Raden Nabilah Putri; Wanda, Dananfi; Kulsum, Iceu Dimas; Lestari, Bony Wiem; Soeroto, Arto Yuwono (Jurnal Respirologi Indonesia, 2025)
Background: Tuberculosis (TB) affects over 10 million people worldwide and causes more than 1.4 million deaths in 2019. Despite improvements in TB treatment, many TB survivors experience ongoing health problems. Post-TB lung disease (PTLD) affects 30-60% of treated patients, leading to chronic respiratory impairments and reduced quality of life. Data on PTLD in Indonesia, a country with a high TB burden, are still scarce. We conducted a preliminary study in Bandung to estimate the burden of respiratory health problems among those who completed TB treatment. Methods: Adults aged 18 years or older with a history of TB treatment and a minimum of 6 months since treatment completion were screened at two primary healthcare centres in Bandung municipality. Data on demographics, previous TB history, and clinical symptoms were collected. Results: From 133 identified TB survivors, 61 eligible patients were interviewed. Persistent respiratory symptoms, such as cough or shortness of breath, were observed in 6 (9.8%) patients. Among these patients, some had abnormal chest x-ray and/or negative Gene Xpert MTB/RIF results. Conclusion: Even after completing treatment, nearly 1 in 10 TB survivors experienced chronic respiratory symptoms. Greater efforts and awareness are needed to improve post-TB wellbeing, especially in high-burden settings like Indonesia.